A general index of inherent risk - Adi Schnytzer; Sara Westreich (Bar-Ilan University, Department of Economics, 2009)
We extend the pioneering work of Aumann and Serrano by presenting an index of inherent riskiness of a gamble having the desirable properties of their index, while being applicable to gambles with either positive or negative expectations. As such, our index provides a measure of riskiness which is of use for both risk lovers and risk aversive gamblers, and is defined for all discrete and a large class of continuous gambles. e analyze abstract properties of our index, and present in addition three empirical applications - roulette, horse betting market and US options traded on financial stocks between 2005 and 2007.
Keywords: 330; Glücksspiel; Pferdesport; Risikopräferenz; USA